The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/aac.49.2.849-852.2005
|View full text |Cite
|
Sign up to set email alerts
|

Selected Arylpiperazines Are Capable of Reversing Multidrug Resistance in Escherichia coli Overexpressing RND Efflux Pumps

Abstract: Several arylpiperazines capable of reversing multidrug resistance (MDR) in Escherichia coli overexpressing acrAB and acrEF but not in pump-deficient mutant strains were identified. 1-(1-Naphthylmethyl)-piperazine, one of the more active compounds, enhanced susceptibility to fluoroquinolones and other agents and increased the intracellular concentration of levofloxacin and ethidium bromide, suggesting efflux pump inhibition as the mechanism of MDR reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
143
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(156 citation statements)
references
References 9 publications
7
143
1
Order By: Relevance
“…5). A number of efflux pump inhibitors phenylalanine-arginine β-naphthylamide (PAβN) [26][27], 1-1-Naphthylmethyl-piperazine (NMP), pyridopyrimidine one and pyrazolopyridines) exerted their inhibitory activity against bacterial efflux pump at concentration range from 70 µg/ml [28] to 100 µg/ml [29], for example, PAβN registered half maximum activity approximately at 70 µg/ml whereas NMP caused EtBr accumulation at 100 µg/ml. An EPI (such as NMP) can also act as antibacterial agent at four-fold (400 µg/ml) concentration to its normal EPI concentration.…”
Section: Typhi Over-expressing Efflux Pumps As Indicated By Etbr Carmentioning
confidence: 99%
“…5). A number of efflux pump inhibitors phenylalanine-arginine β-naphthylamide (PAβN) [26][27], 1-1-Naphthylmethyl-piperazine (NMP), pyridopyrimidine one and pyrazolopyridines) exerted their inhibitory activity against bacterial efflux pump at concentration range from 70 µg/ml [28] to 100 µg/ml [29], for example, PAβN registered half maximum activity approximately at 70 µg/ml whereas NMP caused EtBr accumulation at 100 µg/ml. An EPI (such as NMP) can also act as antibacterial agent at four-fold (400 µg/ml) concentration to its normal EPI concentration.…”
Section: Typhi Over-expressing Efflux Pumps As Indicated By Etbr Carmentioning
confidence: 99%
“…Few compounds were identified as EPIs for AcrAB-TolC, for example: Arylpiperazines were suggested as MDR reversal agent for RND efflux pumps [10], quinolone derivatives were promising EPIs for AcrAB-TolC in Enterobacter aerogenes [11], artesunate enhances the activity of β-lactam antibiotics through inhibition of AcrAB-TolC of E. coli [12], pimozide inhibits the AcrAB-TolC of E. coli [13], and benzothiazoles were identified as potential AcrAB-TolC efflux pump inhibitors (EPIs) in E. coli [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PAbN is able to reverse antimicrobial resistance in some selected MDR Gram-negative bacteria. However, PAbN showed intrinsic antibacterial activity against E. coli strains without expression of AcrAB efflux pumps, and exerted its effect through additional mechanisms unrelated to pump inhibition (Bohnert & Kern, 2005;Pannek et al, 2006;Sáenz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Phe-Arg-b-naphthylamide (PAbN) is an EPI that has been studied by a number of authors (Bohnert & Kern, 2005;Pannek et al, 2006;Sáenz et al, 2004). It has been shown that PAbN is able to reverse antimicrobial resistance in some selected MDR Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation